Effect of aerobic and anaerobic exercise on estrogen level, fat mass, and muscle mass among postmenopausal osteoporotic females - Razzak, Zainab Abdul; Khan, Amna Aamir; Farooqui, Sumaira Imran (International Journal of Health Sciences, 2019)
Objective: The life expectancy of women increases with the advancement in modern medicine, leading them to spent about two decades in menopausal state along with its associated complications. The process of aging triggers a deleterious cascade of physiological changes in the body. Hence, the aim of our study is to determine the effects of both aerobic and anaerobic exercises on estrogen level in postmenopausal osteoporotic females. Methodology: A randomized control trial was conducted among 94 postmenopausal osteoporotic females, randomly divided into two equal groups. The participants in Group A were assigned to perform aerobic exercise, whereas Group B performed resistance exercises. Each group performed exercises for 12 weeks, whereas reading was collected for blood estrogen level, fat mass, and muscle mass before exercise training and after 12 weeks of training. Results: Twelve weeks of aerobic and anaerobic exercise program based on the American College of Sports Medicine (ACSM); frequency, intensity, time, and type protocol has beneficial effect on estradiol level and lean mass, whereas inversely correlated with fat mass of postmenopausal osteoporotic female. Conclusion: The study concluded that 12 weeks of exercise programs was found to be effective in improving estradiol level of postmenopausal osteoporotic female. The efficacy of anaerobic exercise was found to be more potent on estradiol level and lean mass than aerobic exercises as only 36 sessions of resisted exercises performed during a period of 12 weeks provided more significant result than 72 session of aerobic exercises.